1962
DOI: 10.5962/bhl.title.84391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of burning on South Florida range /

Abstract: Recently burned native ranges are characterized by high quality-low volume herbage. Davis and Kirk,-^in tests at the Range Cattle Station, Ona, Florida, found that protein varied from 10 percent in very young wiregrasstype forage to 1.5 to 2.5 percent in old wiregrass. Phosphorus values were usually below 0.10 percent and often below 0.05 percent. Killinger reported as much as 0.18 phosphorus in wiregrass 2 11 days after burning on Leon fine sand in central Florida. Otherwise his findings were similar to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…course of the study had shown a continuing decline in nutritive content with elapsed time after burning (Hilmon and Guides to better utilization of wiregrass range were obtained through observations on effect of rate of stocking. and Lewis, 1962).…”
Section: Chemical Analyses Of Forage Samples Collected During the Conmentioning
confidence: 98%
“…course of the study had shown a continuing decline in nutritive content with elapsed time after burning (Hilmon and Guides to better utilization of wiregrass range were obtained through observations on effect of rate of stocking. and Lewis, 1962).…”
Section: Chemical Analyses Of Forage Samples Collected During the Conmentioning
confidence: 98%
“…1). In three weeks, pineland threeawn comprised 90 percent of the herb weight on an ungrazed range (Hilmon and Lewis, 1962). Panic grasses (Panicurn spp.)…”
Section: Responses Of Range Planis To Firementioning
confidence: 99%
“…iRobertson, 1953iRobertson, , 1954Hofstetter, 1973Hofstetter, , 1974Hofstetter and Parsons, 1975;Wade, Ewel and Hofstetter, 1980;Taylor, 1980). Little information (e.g., Webber, 1935;Laessle, 1942;Davis, 1943;Harper, 1962;Hilmon and Lewis, 1962) exists on the effect of fire on the Florida ridge associations.…”
mentioning
confidence: 99%